(untitled) (Research, Society and Development, 2023)
Chronic Kidney Disease (CKD), whose main cause is type 2 diabetes mellitus (DM2), is defined as a reduction in the glomerular filtration rate below 60ml/min/1.73m2 and/or the presence of albuminuria due to at least 3 months. Currently, the use of sodium-glucose cotransporter-2 (ISGLT2) inhibitors represents a new class of drugs in the treatment of CKD, acting as antagonists of SGLT2 receptors in the kidneys. Objective: This review aimed to analyze and discuss patients with CKD treated with SGLT2 inhibitors and their renal outcomes. A search was carried out for scientific articles indexed in PubMed databases, selecting 190 articles between the years 2018 and 2022. Methodology: The descriptors used, according to “DeCS/MeSH”, were: Chronic Kidney Disease; Glyflozins; Glomerular Filtration Rate; SGLT2 inhibitor. As criteria for inclusion of studies, initially, the following parameters were determined: language of publication in Portuguese and English and type of study “Full Text” and “Randomized Controlled Trial”. Results: The final sample of this review consisted of 13 scientific articles, selected on the PUBMED platform by previously established inclusion criteria. We analyzed 8 double-blind randomized controlled trials, 1 placebo-controlled clinical trial position statement, 2 placebo-controlled clinical trial reviews, and 2 randomized trials. Conclusion: The use of SGLT2 inhibitors improves both renal outcomes and delays the progression of CKD in all KDIGO risk categories, regardless of the presence of type 2 diabetes mellitus.